A cost- benefit analysis on the small-scale aquaponics farming a sustainable food source for community development. - Abella, Danielle May P.; Cular, Anita G. (Danielle May P. Abella, 2018)
Given the rising popularity of aquaponics farming, there have been a recent abundance of literature on its biological components. There is, however, a scarcity of literature on its monetary and sociological aspects. As a consequence, stakeholders may lack the capacity to decide whether aquaponics farming is financially sound or not. The goal of this research is to put together a literature on the costs and benefits of operating a small-scale aquaponics system using locally available resources and recycled materials. Data were collected through personal interviews with aquaponics practitioners in Leyte regarding the costs and benefits they accrued with their own aquaponics systems. With their assistance, an aquaponics set-up was designed to serve as the foundation for this paper's cost-benefit analysis (CBA). This design features a Nutrient-Film Technique (NFT) system which can produce at most 150 heads of vegetables/month and a 200-liter capacity tank. The costs primarily include the capital, labor, operating and opportunity costs, while future earnings, sustainability, nutritional value and farming literacy were considered as benefits in practicing aquaponics. The results in this study show that the benefits generally exceed the costs to be incurred in the long run. Another part of this research provides insights into the applications of aquaponics technology for community development through a survey on the willingness of Ridgeview Park residents--a relocation site of Typhoon Haiyan victims--to produce, either a household-based, and/or community-based aquaponics system. An educational discussion was conducted at the Ridgeview Park Integrated School and self-administered questionnaires were given to the representatives of this study's household participants. Results show that most households were willing to practice both a household-based and community-based set-up. Households were willing to practice aquaponics if some government or non-government funding or initiative were available. On the contrary, the two leading factors that negatively affected their willingness were the costs of setting-up and the lack of technical knowledge on aquaponics. Given the benefits highlighted in this study, government or non-governmental institutions may take insights from this research to conduct more comprehensive studies and/or establish aquaponics systems for marginalized communities to cost-effectively serve local food needs.
A research paper (BASS Economics) -- University of the Philippines, Tacloban.